PELAKSANAAN PENDIDIKAN KARAKTER DALAM KEGIATAN LATIHAN DASAR KEPEMIMPINAN SISWA DI SMP NEGERI 1 KAYUTANAM - Arisman Sabir; Desi Fitria; Dedek Helida Pitra; Marlinda Astuti; Superdi S (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
This research is motivated by the existence of the types of characters that are formed in basic student leadership training activities at SMPN 1 Kayutanam, obstacles that occur in the implementation of character education in basic student leadership training activities at SMPN 1 Kayutanam and efforts to overcome obstacles in implementing character education in basic student leadership training activities at SMPN 1 Kayutanam. This type of research is a qualitative descriptive method, which was taken using a purpose sampling technique. The data were collected by means of observation, interviews, and documentation studies. The data validity test used is source triangulation. Data analysis techniques in this study were carried out using techniques from Milles and Huberman, namely: (1) data collection process, (2) data reduction, (3) data presentation and (4) conclusion drawing or verification. Informants in this study were principals, teachers and also students who took part in basic student leadership training activities. The results showed that: (1) The types of characters formed in the basic student leadership training activities at SMPN 1 Kayutanam were: (a) Discipline character formation, (b) responsibility, (c) environmental care, (d) religious, (e) appreciate achievements. (2) The obstacles that occur in the implementation of character education in basic student leadership training activities at SMPN 1 Kayutanam are: (a) not all students are interested and interested in participating in extracurricular activities. Basic student leadership training, (b) There are still many parties who underestimated students' basic leadership training activities, (c) lack of basic student leadership training or lack of interest in extracurricular activities for student leadership basic training at school, (3) Efforts to overcome obstacles to implementing character education in student leadership basic training activities at SMPN 1 Kayutanam, namely: (a) Providing strict rules for students, (b) Designing learning strategies that have regular character planting programs, (c) Routinely instilling a good attitude, (d) Always admonishing (e) Always being a good teacher .